From the north into the Himalayan–Hengduan Mountains: fossil‐calibrated phylogenetic and biogeographical inference in the arctic‐alpine genus Diapensia (Diapensiaceae). (7th April 2016) - Hou, Yan; Bjorå, Charlotte Sletten; Ikeda, Hajime; Brochmann, Christian; Popp, Magnus
Abstract: Aim: Many arctic species are believed to be descendants from ancestors that migrated northwards from high mountains during the formation of the modern arctic biome 2–3 million years ago (Ma). Here, we test whether this hypothesis is consistent with the biogeographical history of the arctic‐alpine genus Diapensia, which shows a disjunction between the Arctic and the Himalayan–Hengduan Mountains (HHM). Location: The Arctic/sub‐Arctic and the HHM. Methods: We used the plastid DNA (pDNA) sequences mat K and rbc L and seven Ericales fossils to date the origin of Diapensia . Sequences of four pDNA markers and the nuclear ribosomal internal transcribed spacer from 56 Diapenisa accessions were then used to reconstruct the phylogenetic relationships and time of divergence among Diapensia species. Results: Diapensia consists of three major clades; two corresponding to the two arctic species, and one containing the two HHM species sampled. Both the pDNA tree and the species tree resolved the amphi‐Beringian D. obovata as sister to a clade that included D. lapponica that has an amphi‐Atlantic distribution and the HHM clade. The two arctic species were estimated to have originated in the Middle Miocene‐Early Pliocene ( D. obovata : 8.3 Ma, 95% highest posterior probability density (HPD) 4.0–13.5 Ma; D. lapponica : 7.1 Ma, 95% HPD 4.1–10.0 Ma), long before the formation of the modern arctic biome. In contrast, species divergence in the HHM clade was found to be very recent (0.5 Ma, 95% HPD 0.2–0.9 Ma; Early‐Middle Pleistocene). Main conclusions: Our results reject an HHM origin of the arctic Diapensia and rather suggest that the ancestor of the D. lapponica /HHM clade migrated southwards into the HHM. This study adds to a growing body of evidence suggesting that arctic plant lineages have diverse origins in time and space.